2D foaming of ultrathin MXene sheets with highly conductive silver nanowires for wearable electromagnetic interference shielding applications owing to multiple reflections within created free space. Issue 3 (22nd July 2020) - Yin, Hongyu; Bi, Lili; Wu, Zhen; Wang, Guixin; Li, Mian; Zhou, Xiaobing; Ji, Shulin; Zhang, Wang; Peng, Yongwu; Pan, Jun; Ye, Cui; Huang, Qing
Abstract: Interest has been growing in electromagnetic interference (EMI) shielding materials in view of soaring EM radiation and its pollution control, which is necessary for public health and normal communication. To realize high EMI shielding effectiveness (SE), two factors of high electrical conductivity and strong multiple reflections are quite important. However, it is still a big challenge to obtain these two characteristics simultaneously in one material system. Here, we present a lightweight composite film integrating silver nanowires (AgNWs) as the skeleton and MXene as the covering decoration (AgNWs/Ti3 C2 Tx ) for foaming structure. The composite film exhibits a low density of about 1 g cm −3 and an electrical conductivity of up to 15 038 S cm −1, which give a superiorly high specific EMI SE per unit thickness of 270 997 dB · cm 2 g −1, and an EMI SE of 41.3 dB at a thickness of 1.2 μ m (or 96.7 dB at a thickness of 40 μ m) in the X-band. A film formation method of positive pressure filtration helps to easily control free space created during foaming for adequate EM wave scattering, yet remaining within the skin depth and strong multiple reflections have been achieved. The superior EMI shielding properties make the lightweight AgNWs/Ti3 C2 Tx composite film a promising candidate in high-end applications.